One‐Step Pyrolysis to Synthesize Non‐Graphitic Nitrogen‐Doped 2D Ultrathin Carbon Nanosheets and Their Application in Supercapacitors. Issue 10 (16th May 2019) - Guo, Wen; Zhou, Yansong; Pang, Lei; Chen, Zhen; Dong, Yahao; Bi, Jiajun; Ming, Shujun; Li, Tao
Abstract: Non‐graphitic nitrogen plays a significant role in determining the electrochemical performance of carbon materials in the field of energy storage. However, the synthesis of carbon materials with a high level of non‐graphitic nitrogen doping is still a great challenge. In this paper, a facile one‐step pyrolysis approach was developed to synthesize 2D carbon nanosheets with a ultrahigh non‐graphitic nitrogen content. Through an ingenious design, g‐C3 N4 and NH3, both generated during the pyrolysis process, play major roles in the generation of the non‐graphitic nitrogen‐doped carbon nanosheets. The intermediate g‐C3 N4 acts as both a self‐sacrificial template and a nitrogen source, whereas NH3 offers a nitrogen‐enriched chemical atmosphere. Benefiting from the high pyridinic‐nitrogen content of the maternal g‐C3 N4 and the reductive atmosphere of NH3, the as‐prepared carbon nanosheets exhibit a strikingly high non‐graphitic nitrogen content (up to 17.36 wt.%); also, thanks to the g‐C3 N4 self‐sacrificial template, the as‐synthesized carbon nanosheets are 2D with an ultrathin thickness (3–4 nm) and a porous structure. These novel features make the as‐prepared carbon nanosheets an excellent supercapacitor electrode material in terms of superior specific capacitance (316.8 F g −1 at 1 A g −1 ), excellent cycling stability (without obvious capacitance loss after 10 000 cycles at 10 A g −1 ) and high energy density (up to 10.56 Wh kg −1 at a power density of 500 W kg −1 ). This work provides a new idea to prepare non‐graphitic nitrogen enriched carbon materials. Abstract : Material matters : Ultrathin 2D carbon nanosheets with an ultrahigh non‐graphitic N‐doping level are synthesized through a one‐step pyrolysis process. Electrochemical measurements show that the obtained non‐graphitic nitrogen content, novel 2D ultrathin nanosheet morphology, and porous structure can enhance the supercapacitive performance of the materials.